APPLICATION OF INTERACTIVE LEARNING MEDIA MATHEMATICS ASSISTED BY PREZI APPLICATION TO IMPROVE LEARNING OUTCOMES OF GRADE IV ELEMENTARY SCHOOL STUDENTS - Fisqi Sabila Astuti; Kunti Dian Ayu Afiani; Lilik Binti Mirnawati (Prima: Jurnal Pendidikan Matematika, 2023)
This study aims to determine the process of applying and improving learning outcomes, activities in the use of prezi applications in grade IV students of MI Muhammadiyah 25 Surabaya. This type of research is Class Action Research (PTK). The subjects of this study are 26 students of grade IV MI Muhammadiyah 25 Surabaya for the 2022 academic year. This research can improve mathematical performance, especially in expressing mathematical sentences. The data collection process is carried out through observation and testing methods. The implementation of this study took place in two cycles. The results obtained from the action on cycle I averaged 53.8% increased to 80.8% in cycle II. The improvement in cycle II has reached classical completion so that there is no need for the next cycle, so it can be concluded that the application of interactive mathematics learning media assisted by the prezi application can improve student learning outcomes and student activities.